A numerical study: Transitional hydrodynamic behaviour of a moored barge in different ultra-shallow water depths of Malaysia - Patel, M.S.; Azizan, N.; Liew, Mohd. Shahir; Mustaffa, Zahiraniza; Ali, M.O.; Whyte, Andrew (2020)
Background: Malaysia has most of its oil reservoirs in the South China sea. The water depth ranges from 50 m to 200 m. The effects of ultra-shallow water are of prime importance in the exploration of marginal oil fields. Hence, there is an increasing demand for understanding the hydrodynamic behavior of FPSO in ultra-shallow water depths.